2021
DOI: 10.3390/genes12050756
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Peptide Hormones Discovered in the 21st Century in the Regulation of Adipose Tissue Functions

Abstract: Peptide hormones play a prominent role in controlling energy homeostasis and metabolism. They have been implicated in controlling appetite, the function of the gastrointestinal and cardiovascular systems, energy expenditure, and reproduction. Furthermore, there is growing evidence indicating that peptide hormones and their receptors contribute to energy homeostasis regulation by interacting with white and brown adipose tissue. In this article, we review and discuss the literature addressing the role of selecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 164 publications
0
14
0
Order By: Relevance
“…The expression of NPB and NPBWR1 mRNA in rat zona glomerulosa (ZG) and ZF/R cells was confirmed by an independent study, which additionally showed that both genes were expressed in the adrenal medulla (AM) [ 51 ]. The expression of NPB and NPBWR1 and NPBWR2 mRNA was detected in ZG and ZF/R cells of adrenal cortexes [ 4 ]. The same study showed that NPB failed to modulate basal aldosterone secretion from zona granulosa cells [ 26 ].…”
Section: The Role Of Npb In Regulating Glucose and Lipid Metabolismmentioning
confidence: 99%
See 1 more Smart Citation
“…The expression of NPB and NPBWR1 mRNA in rat zona glomerulosa (ZG) and ZF/R cells was confirmed by an independent study, which additionally showed that both genes were expressed in the adrenal medulla (AM) [ 51 ]. The expression of NPB and NPBWR1 and NPBWR2 mRNA was detected in ZG and ZF/R cells of adrenal cortexes [ 4 ]. The same study showed that NPB failed to modulate basal aldosterone secretion from zona granulosa cells [ 26 ].…”
Section: The Role Of Npb In Regulating Glucose and Lipid Metabolismmentioning
confidence: 99%
“…In addition, such peptides are present in the circulation and in numerous peripheral tissues. There is growing evidence indicating that peptides that control appetite (e.g., kisspeptin, orexins, spexin, adropin, apelin, phoenixin, ghrelin, amylin, and pancreatic peptides) also modulate the endocrine activity of endocrine glands as well as lipid and glucose metabolism [ 1 , 2 , 3 , 4 , 5 , 6 ]. Moreover, some peptides are involved in regulating the endocannabinoid system and, through it, food intake, e.g., hemopressin, a small peptide derived from the α-chain of hemoglobin, reduces appetite through increased levels of endocannabinoids [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…The SPX mature peptide is a tetradecapeptide that is flanked by two dibasic protein cleavage sites (RR and GRR), and its amino acid sequence is highly conserved in various vertebrates, with only one amino acid substitution at position 13 between tetrapods and teleosts (3)(4)(5). Consistent with its widespread distribution in different tissues of teleosts and other vertebrates, SPX participates in a variety of physiological functions, such as glucose homeostasis, lipid metabolism, feeding, digestion, reproduction, among others (6)(7)(8)(9)(10). Preliminary evidence in teleosts and other vertebrates have indicated that SPX binds to the membrane galanin receptor 2 (Galr2) and Galr3, but not Galr1, to exert its functions (11)(12)(13).…”
Section: Introductionmentioning
confidence: 97%
“…Endogenous bioactive peptides are ubiquitous in higher organisms and involved in many physiological processes, ranging from controlling metabolism [1] to neural signaling [2]. Many of these peptides are secreted and exert their function by binding to membrane-expressed receptor proteins, such as G-protein coupled receptors (GPCRs) and are thus appealing for drug development [3].…”
Section: Introductionmentioning
confidence: 99%